Effects of heavy metals （Pb^2＋ and Cd^2＋） on the ultrastructure, growth and pigment contents of the unicellular cyanobacterium Synechocystis sp. PCC 6803 - K. K. I. U. Arunakumarat 张学成 (Chinese journal of oceanology and limnology, 2009)
The unicellular cyanobacterium Synechocystis sp. PCC 6803, a model organism known for its unique combination of highly desirable molecular genetic, physiological and morphological characteristics, was employed in the present study. The species was cultured in BG11 liquid medium contained various initial concentrations of Pb^2＋ and Cd〉 （0, 0.5, 1, 2, 4, 6 and 8 mg/L）. The experiment was conducted for six days and the metal induced alterations in the ultrastructure, growth and pigment contents were assessed. Alterations in the ultrastructure of the Synechocystis sp. PCC 6803 cells became evident with the increased （〉4 mg/L Pb^2＋） metal concentration. The photosynthetic apparatus （thylakoid membranes） were found to be the worst affected. Deteriorated or completely destroyed thylakoid membranes have made large empty spaces in the cell interior. In addition, at the highest concentration （8 mg/L pb^2＋）, the polyphosphate granules became more prominent both in size and number. Despite the initial slight stimulations （0.2, 3.8 and 6.5% respectively at 0.5, 1 and 2 mg/L pb^2＋）, both metals inhibited the growth in a dose-dependent manner as incubation progressed. Pigment contents （chlorophyll a, 13 carotene and phycocyanin） were also decreased with increasing metal concentration. Cells exposed to 6 mg/L Pb^2＋, resulted in 36.56, 37.39 and 29.34% reductions of chlorophyll a, 13 carotene and phycocyanin respectively over the control. Corresponding reductions for the same CdZ＋concentrations were 57.83, 48.94 and 56.90%. Lethal concentration （96 h LC50） values （3.47 mg/L Cd^2＋ and 12.11 mg/L Pb^2＋） indicated that Synechocystis sp. PCC 6803 is more vulnerable to Cd^2＋ than Pb^2＋.